Comparative assessment of species identification methods for European Salicornia sources: a multifaceted approach employing morphology, nuclear DNA content, phylogenetic markers, RNA topology, and SSR fingerprinting - Fussy, Andre; Austoni, Samuele; Winkelmann, Traud; Papenbrock, Jutta (Frontiers in Plant Science, 2025)
Accurate identification of Salicornia species is a fundamental prerequisite for their potential usability and domestication. This study utilized a multifaceted methodological approach integrating morphological, cytogenetic, and molecular techniques to identify species from available European Salicornia sources. The following methods were compared: nuclear DNA content analysis; application of marker-based DNA barcoding via four common Salicornia markers; investigations of RNA topologies of these marker sequences by predicting theoretical secondary structures; utilization of diagnostic single-nucleotide polymorphism (SNP) positions within the external transcribed spacer (ETS) marker sequences for European Salicornia taxa; comparison of three promising microsatellite (SSR) markers regarding their ability to differentiate Salicornia subspecies; and evaluation of morphological data on habitus and flower characteristics utilizing a Salicornia identification key. The results demonstrate that ETS marker analysis offers reliable and cost-effective species determination, with SNP comparisons being more user friendly than phylogenetic trees are, and microsatellite markers can be differentiated down to the subspecies level via fragment length differences. However, microsatellite analysis alone is not suitable for primary species identification. DNA content can provide a rough estimation of potential species and is already more reliable than morphological methods. The differentiation among species is crucial for creating transparency for farmers and consumers and for initiating breeding processes, particularly within the context of frequent misidentification.